Bioethics and education to the Gospel of Life. - Grocholewski, Zenon (Medicina e Morale, 2004)
The article deals with the theme of the education in bioethics. It is divided in three parts; each part is faced departing from the consideration that today it is very important to develop an authentic education to the respect and the promotion of life in the places where such educational processes happens: family, school and in the other educational institutions. In the first part of the article, the Author underlines the cultural and educational horizon of our times concerning the bioethics, that it has become a "public" discipline, involving also the educational field. In the second part of the article the issue of the anthropological fundament of the education is faced. The Church thinks that this fundament is constituted by human person and her unique value. After a look about the necessity that the education of the man be integral, or rather that keep in mind the whole man in his entirety, the Author concludes with some observations for up-to-dating the bioethics in the educational field. More times, the Holy Father has invited who have an educational role in the society to fight for a culture of life. In such sense, the school should become a privileged battleground, keeping in mind some fundamental presuppositions: the individualization of the ethical-moral implications that spring from the progress of the sciences concerning the life of the man and the other species, and from the use of the biotechnologies; the planning of the educational methods to approaching bioethics, keeping in mind the interdisciplinarity of the problems; the initial and permanent education of the teachers.